Physical fitness as one of the directions of the historical development of physical culture - Сутула, Василь; Луценко, Лариса; Жадан, Андрій; Сутула, Анастасія (Slobozhanskyi Herald of Science and Sport, 2018)
Vasyl Sutula, Larisa Lutsenko, Andrey Zhadan & Anastasiia Sutula Purpose: to reveal the cultural and historical origins of the concept of "physical fitness". Material & Methods: an analysis of specialized literature covering various aspects of the development of the field of human activity associated with the use of physical exercises. Results: at the turn of the 20th century, the term "physical culture" was used as a generalising name for the three areas of people’s activities related to the use of physical exercises: activities aimed at bringing the body in line (physical fitness) activities aimed at developing physical strength and body build (bodybuilding) activities aimed at improving through the use of physical exercises (therapeutic physical culture). Conclusion: In terms of the theory of physical culture of physical fitness is seen as a particular socio-cultural phenomenon, which is a historically conditioned human activity involving the use of physical exercise at their leisure, and individual and socially significant results of such activities.